2021
DOI: 10.1108/jcm-08-2020-4021
|View full text |Cite
|
Sign up to set email alerts
|

When is more really more? The effect of brands on choice overload in adolescents

Abstract: Purpose Research on choice overload with adult participants has shown that the presence of a brand significantly mitigates the phenomenon. The purpose of this study is to investigate whether these findings can be expanded to a population of adolescents, where it has already been shown that choice overload occurs in a similar way as adults. Design/methodology/approach Studies 1 and 2 aim to test whether the presence of a brand name mitigates the adverse consequences of choice overload in adolescents. In line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 64 publications
1
19
0
Order By: Relevance
“…Results demonstrated that participants were experiencing choice overload only in this latter condition, whereas in the condition in which the same phones were associated to brands, participants deal well with large assortments. The same findings have been replicated with a population of adolescents (Misuraca et al, 2021a).…”
Section: Moderators Of Choice Overloadsupporting
confidence: 57%
See 1 more Smart Citation
“…Results demonstrated that participants were experiencing choice overload only in this latter condition, whereas in the condition in which the same phones were associated to brands, participants deal well with large assortments. The same findings have been replicated with a population of adolescents (Misuraca et al, 2021a).…”
Section: Moderators Of Choice Overloadsupporting
confidence: 57%
“…A further important moderator of choice overload is the presence of brand names. As recently demonstrated by researchers in psychology and consumer behavior, choice overload occurs only when options are not associated with brands, whereas it appears when the same choice options are presented without any brand names (Misuraca et al 2019;Misuraca et al, 2021a). In one of these experiments, adult participants had to make a choice among either 6 or 24 different mobile phones, described along six different technical characteristics (e.g., battery duration, camera resolution, etc).…”
Section: Moderators Of Choice Overloadmentioning
confidence: 99%
“…Another way to help people act more rationally and, thus, to increase their willingness to adhere to COVID-19 preventive behaviors is the use of clear and effective communication, which takes into consideration the limitations of human cognition [ 69 ]. In particular, communication should avoid information and choice overload [ 70 , 71 , 72 , 73 ]. Communication should be simple, and it should illustrate what people should do and not do, in a way that it is easy to understand for everyone.…”
Section: Solutionsmentioning
confidence: 99%
“…In our opinion, the most interesting focus of our study concerns the elicitation of prosocial priming in an online context, such as e-mail. Most research on priming in an online context has been carried out mainly in marketing (Smith and Wheeldon, 2001;Misuraca et al, 2019Misuraca et al, , 2021aDennis et al, 2020;Tanford et al, 2020). We do not know of any study investigating the impact of priming on bystander apathy in the online context.…”
Section: Discussionmentioning
confidence: 99%